PERLINDUNGAN TENTARA ANAK DALAM KONFLIK BERSENJATA DITINJAU DARI SEGI HUKUM HUMANITER INTERNASIONAL - Seokotjo Hardiwinoto, Bintang Kinayung Ingtyas, Joko Setiyono, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
International armed conflict in Republic Democratic Congo occurs as reaction from the people's saturation caused by the authoritarian leadership of President Mobutu Sese Seko. This conflict is exacerbated when Tutsi tribe survivor from the Hutu tribe's felony in Rwanda escape to the border, Tutsi tribe helped by rebel groups of the Republic Democratic Congo and they alliances to overthrow the Government of President Mobutu Sese Seko. The Government also recruited the Hutu tribe to against the opponent. Economic of the Republic Democratic Congo decreased by this conflict. The poverty causes Government'sÂ difficulties to paid the salary of the soldiersÂ and it's the beginning of child soldiers recruitment.Â The Republic Democratic Congo has ratified some instruments of child recruitment on armed conflict, specially as child soldiers. The instrument related is to protect and prevent of recruiting child soldiers.